Media Coverage of Firms: Background, Integration, and Directions for Future Research - Graf-Vlachy, Lorenz; Oliver, Abbie Griffith; Banfield, Richard; König, Andreas; Bundy, Jonathan (Journal of Management, 2020)
Over the past years, media coverage of firms has received significant scholarly attention. However, the resulting literature is spread across multiple disciplines and, therefore, varies with regard to its theoretical underpinnings and contextual settings. This makes it challenging for scholars to understand the contributions of this literature, to identify areas of inquiry, and to develop an encompassing research agenda. In this review, we address these issues by surveying the diverse literature on media coverage of firms to develop an integrative framework of the antecedents and consequences of media coverage that highlights paths for future research. Specifically, we identify the three theoretical perspectives—economic, institutional, and social-psychological—that the literature generally assumes on the news media. In addition, we highlight differences between strategy, finance, governance, and crisis contexts and review results from articles examining media coverage of firms in aggregate. In each context, we identify the primary functions of the news media as well as antecedents and consequences of media coverage. We proceed to develop an integrative framework for media coverage of firms by building on these findings and by examining the empirical methods used to measure media coverage, particularly regarding the measurement of specific coverage attributes. We highlight the gaps in current knowledge that our framework exposes and derive opportunities for future research that can further scholars’ and practitioners’ understanding of firm media coverage.